HealthPathways implementation on type 2 diabetes: A programmatic evaluation (HIT2 evaluation). Issue 2 (15th April 2019) - Chow, Josephine S.F.; Gonzalez-Arce, Veronica Eugenia; Tam, Chun Wah Michael; Neville, Ben; McDougall, Alan
Abstract : Purpose: The purpose of this paper is to appraise the development, implementation and acceptance of HealthPathways (HP), specifically in Type 2 Diabetes Mellitus (T2DM), at different levels of the health system in a large metropolitan Local Health District in Australia. Design/methodology/approach: This study used a programmatic approach and mixed methods including literature reviews, site visits, semi-structured interviews of stakeholders and General Practitioners (GPs), and surveys (GPs and patients) to better understand the development, implementation and acceptance of T2DM pathways. Findings: Results from this study indicate that 63 percent ( n =37) of all survey respondents use HP and nearly half (47 percent) use HP in caring for a patient with diabetes. More than 80 percent of the health professionals found HP a useful tool, which has improved the quality of care, keeps them informed and supports diagnostics process. The use of website has led to an improvement in referral quality (69 percent), has assisted in the provision of more healthcare in the community (87 percent) and made their job easier. Thematic analysis from stakeholder interviews ( n =12) emphasizes the importance of established collaborations and the need for standardized tools with common priorities and transparency in processes. Practical implications: This study has provided insight into the details of delivery of integrated healthcare using HP. It provides a preliminary analysis of the lessons learnt for the implementation of HP. Originality/value: The results of this study will be ideally placed to inform future policy amendments in the area of integrated healthcare as well as serving as a guide on implementing HP in the future.